암치료 보조제로서 녹차 폴리페놀성 화합물의 가능성 - 이지환; 이우정; 이승용; Noriko Yamabe; 김수남; 조은주; 김현영; 강기성 (대한암예방학회, 2012)
In the present study, in vitro beneficial effects of tea catechins on gastrointestinal cancer as well as nephrotoxicity were explored. Antioxidant activities of 6 green tea catechins were evaluated by 1,1- diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity test. To evaluate the anticancer effect, the effect of (-)-epigallocatechin-3-gallate (EGCG) as a representative tea catechin was investigated in HCT-116 human colorectal cancer and AGS human gastric cancer cells. Protective effect of EGCG against oxidative renal cell damage was measured using radical generator, 2,2'-azobis (2-amidinopropane) dihydrochloride in LLC-PK1 cells. EGCG showed the strongest DPPH radical scavenging activity and completely decreased the gastrointestinal cancer cell viability at 10 μM. Moreover, EGCG protected renal epithelial LLC-PK1 cells from oxidative damage in the dose-dependent manner. Therefore, EGCG has beneficial effects on cancer therapy by its anticancer effect and by reducing oxidative stress-induced nephrotoxicity.